2000
DOI: 10.1046/j.1464-5491.2000.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and social factors are related to increased morbidity and mortality rates in diabetic patients

Abstract: Environmental factors affect diabetes outcomes; increased morbidity and mortality rates in diabetic patients are related to socio-economic and ethnic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 19 publications
(21 reference statements)
6
66
1
5
Order By: Relevance
“…This argument would lead to the conclusion that higher socioeconomic status is associated with worse metabolic control, which has not been observed [32]. When we tested subcohorts defined by parameters with some socioeconomic impact (age, sex, area of residency), the difference between SMBG and non-SMBG in terms of outcome remained.…”
Section: Hr (95% Ci)mentioning
confidence: 92%
“…This argument would lead to the conclusion that higher socioeconomic status is associated with worse metabolic control, which has not been observed [32]. When we tested subcohorts defined by parameters with some socioeconomic impact (age, sex, area of residency), the difference between SMBG and non-SMBG in terms of outcome remained.…”
Section: Hr (95% Ci)mentioning
confidence: 92%
“…In the general population, mortality is greater in those from a more disadvantaged socioeconomic situation, principally as a result of cardiovascular disease [16]. In the presence of diabetes, however, mortality rates are significantly greater in individuals who live in relatively deprived areas [17]. Furthermore, depression has been found to be associated with a 2.3-fold increase in mortality vs no depression in individuals with diabetes [18].…”
Section: Introductionmentioning
confidence: 99%
“…SES has been associated with DFD, whereby lower SES status correlated with higher DFD prevalence [45,53,67]; with similarities as certain study types and methods demonstrated significant findings.…”
Section: Socio-economic Status and Diabetic Foot Disease Developed Comentioning
confidence: 81%
“…Furthermore, across all hospitalisations, Aboriginal and Torres Strait Islanders residing in lower SES areas had higher admission levels, again reflecting a causal link between social factors and DFD hospitalisation ( Figure 2). here is existing literature in developed countries [45,67] demonstrating a 1.7 fold increased risk of experiencing DFD when living in disadvantaged areas [53]. In a similar Australian study, those who resided in the most disadvantaged areas had higher rates of DFD-related hospitalisation [71].…”
Section: Diabetic Foot Disease and Socio-economic Statusmentioning
confidence: 92%
See 1 more Smart Citation